2009
DOI: 10.1093/carcin/bgp020
|View full text |Cite
|
Sign up to set email alerts
|

Dietary variables associated with DNA N7-methylguanine levels and O6-alkylguanine DNA-alkyltransferase activity in human colorectal mucosa

Abstract: Components of human diets may influence the incidence of colorectal adenomas, by modifying exposure or susceptibility to DNA-damaging alkylating agents. To examine this hypothesis, a food frequency questionnaire was used to assess the diet of patients recruited for a case-referent study where biopsies of normal colorectal mucosa were collected during colonoscopy and subsequently analysed for DNA N7-methylguanine (N7-MeG) levels, as an indicator of exposure, and activity of the DNA repair protein O 6 -alkylguan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…There are no previous reports of the effect of dietary protein on the alkyl-induced DNA adduct O 6 MeG. In a case study examining biopsies of normal colorectal mucosa, red meat was found to be a risk factor in the formation of N 7 -methylguanine (N 7 -MeG) but that adduct is not oncogenic (41). A randomized crossover trial comparing high red meat, vegetarian, and high red meat/high fiber diets showed marked increases of the O 6 -carboxymethylguanine (O 6 CMG) in exfoliated colon cells when healthy volunteers consumed a high red meat diet (9); however, exfoliated cells might acquire new adducts in the lumen with more direct exposure to protein fermentation products.…”
Section: Discussionmentioning
confidence: 99%
“…There are no previous reports of the effect of dietary protein on the alkyl-induced DNA adduct O 6 MeG. In a case study examining biopsies of normal colorectal mucosa, red meat was found to be a risk factor in the formation of N 7 -methylguanine (N 7 -MeG) but that adduct is not oncogenic (41). A randomized crossover trial comparing high red meat, vegetarian, and high red meat/high fiber diets showed marked increases of the O 6 -carboxymethylguanine (O 6 CMG) in exfoliated colon cells when healthy volunteers consumed a high red meat diet (9); however, exfoliated cells might acquire new adducts in the lumen with more direct exposure to protein fermentation products.…”
Section: Discussionmentioning
confidence: 99%
“…Here, individuals in the lowest tertile of total dietary folate intake (<170 μg/1,000 kcal per day) had significantly lower NER repair capacity compared with those in the upper tertile (>225 μg/1,000 kcal per day). MGMT activity, measured in normal human colon biopsies is inversely linked to vegetable consumption, whereas low dietary folate intake is specifically associated with high levels of alkylation damage (Billson et al 2009). Whereas folate deficiency appears to affect DNA repair detrimentally, it is unclear whether increasing folate intake can improve repair.…”
Section: Folate Status and Colon Cancer Riskmentioning
confidence: 99%
“…Some dietary agents, such as genistein and epigallocatechin-3-gallate showed the ability to reactivate some methylation-silenced genes in cancer cells like MGMT due to a direct inhibition of DNA methyltransferase (Fang et al, 2005;Fang et al, 2003). Recently, Billson et al, (2009), demonstrated that a high vegetable intake in humans decreases MGMT activity in normal colorectal mucosa. To understand the real role of dietary agents on chemotherapy when in combination with alkylating drugs more studies are need.…”
Section: Effects Of Phytochemicals Through Dna Repair Modulation and mentioning
confidence: 99%